SPIRITUAL SHRINES OF THE ASTRAKHAN KAZAKHS AND COMMEMORATIVE PRACTICES - Нургалиева, Агила Мустахимовна (Вестник ЗКУ, 2022)
The article is devoted to the description of the main types of sacred objects of the Kazakhs located in the Astrakhan region of Russia. Legends and traditions related to these sacred places and the names of the great sons of the Russian and Kazakh lands are also considered. Commemorative practices as a form of visualization of cultural memory are analyzed. Some of them go back to the "cultural archetypes" associated with the cult of ancestors. The initiators and organizers of others were the political and cultural elite of Russia and Kazakhstan. This can be seen as a conscious reconstruction of historical memory in the form of traditions.